The role of talus size distribution & the frequency of transport in wide and narrow valleys on bedrock valley widening: Buffalo National River, Arkansas - Groeber, Olivia Hermine (Kansas State University, 2022)
Bedrock river valleys are a valuable resource from which we learn about historic climactic changes, shifts in discharge and sediment inputs, movement of the river channel, and bedrock valley widening processes. Bedrock river valleys are often found in two end-member states: narrow, canyon-like bedrock valleys, and wide, bedrock valleys many times wider than the river channel. So far, little research has been done to determine the controls on bedrock river widening. Previous work has pointed to lithology and upstream drainage area as the main controls on bedrock valley width, but these do not take into account specific valley widening processes. I tested a conceptual model describing two end-member processes to create bedrock river valleys. First, the river laterally erodes and undercuts the bedrock valley wall, eventually leading to collapse. Second, the river transports the collapsed talus blocks and moves them from the wall, allowing the river access to the wall again for continued undercutting. If a river at different flow regimes cannot move a talus block, the valley wall is shielded from lateral erosion until the grain size is small enough to be moved, thus preventing bedrock valley widening. The Buffalo River is an ideal bedrock river to address this question as it has both wide and narrow bedrock valleys in similar lithologies. I measured the grain sizes of talus blocks at the base of bedrock valley walls, grain sizes of bedload, and bankfull width at 40 sites in wide and narrow valleys. If talus block size contributes to the development of wide bedrock valleys, I would expect that I would find large talus in the narrow valley and smaller talus grains in the wide valley. Locations in the narrow valleys have larger talus grain sizes than locations in the wide bedrock valleys for our field site in Buffalo National River. The wide valleys had a greater ability to move talus blocks in the 100 and 1,000-year floods, but I found that the narrow valleys could hardly move talus grains even in the 1,000-year floods. These results support the conceptual model that talus block size, in conjunction with many other factors, is a control on bedrock valley width.
Keywords: Buffalo National River; Bedrock river; Talus piles; Valley widening; Rock movement; Lateral widening